A Compact Head‐Mounted Endoscope for In Vivo Calcium Imaging in Freely Behaving Mice. Issue 1 (26th June 2018) - Jacob, Alexander D.; Ramsaran, Adam I.; Mocle, Andrew J.; Tran, Lina M.; Yan, Chen; Frankland, Paul W.; Josselyn, Sheena A.
Abstract: Miniaturized fluorescence microscopes for imaging calcium transients are a promising tool for investigating the relationship between behavior and population‐level neuronal activity in rodents. However, commercially available miniature microscopes may be costly and, because they are closed source, may not be easily modified based on particular experimental requirements. Here, we describe how to build and use a low‐cost compact head‐mounted endoscope (CHEndoscope) system for in vivo calcium imaging. The CHEndoscope uses an implanted gradient index lens along with the genetically encoded calcium indicator GCaMP6 to image calcium transients from hundreds of neurons simultaneously in awake behaving mice. This system is affordable, open source, and flexible, permitting modification depending on the particular experiment. This article describes in detail the assembly, surgical implantation, data collection, and processing of calcium signals using the CHEndoscope system. The aim of this open framework is to provide an accessible set of miniaturized calcium imaging tools for the neuroscience research community. © 2018 by John Wiley & Sons, Inc.